Human Polyomaviruses and Papillomaviruses - Ugo Moens (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The interest in human polyomaviruses (HPyV) has seen a renaissance because of new species that have been isolated and their previously unknown association with diseases. Likewise, the increasing evidence for the association of human papillomaviruses (HPV) with oropharyngeal cancer has sparked the attention of researchers and clinicians. The Special Issue “Human Polyomaviruses and Papillomaviruses” presents studies describing the nuclear egress of BK polyomavirus mediated by the viral agnoprotein and the cellular -SNAP protein. In addition, a study examines the promoter activity of two different variants of human polyomavirus 9 in different cell lines. This Special Issue offers an interesting perspective on the epidemiology of HR-HPV in different cancers and on the mechanisms by which these viruses target host cell proteins to replicate their genome, express their genes, interfere with autophagy, and induce cancer. Other topics that are highlighted include the role of co-factors, such as smoking and co-infection, novel therapeutic strategies, and surface immunoregulatory proteins, chemokines, and cytokines as possible biomarkers to determine the stage of a tumor and to predict clinical outcomes.